2018
DOI: 10.1016/j.foodcont.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acid ingredients in marinades containing different types of sugar on the formation of heterocyclic amines in grilled chicken

Abstract: The aim of the study was to determine the use of alternative organic acids in formulating marinade ingredients to reduce heterocyclic amines (HCA) in grilled chicken (satay). Samples were marinated with table sugar, brown sugar, and honey with the addition of tamarind, lemon, lime, and calamansi for 24 h at 4 °C. The pH readings before and after marinating were measured. HCA concentrations before and after grilling were quantified. There was a significant difference (p<0.05) in the combined HCAs among the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Hence, scientists around the world have recently focused on the investigation about how to reduce HAAs in heat‐processed foods and attempted to find possible strategies to inhibit the formation of HAAs (Chen et al., ; Oz & Seyyar, ; Rahman, Sahar, Khan, & Nadeem, ; Tengilimoglu‐Metin & Kizil, ). To date, several inhibitory strategies such as adjusting cooking methods (Guo et al., ; Oz & Kotan, ; Oz & Zikirov, ; Oz, Kaban, & Kaya, ; Soladoye et al., ), changing thermal treatments (Raza, Shabbir, Khan, Suleria, & Sultan, ; Shabbir, Raza, Anjum, Khan, & Suleria, ), adding antioxidants or substances which have inhibiting effect on the formation of HAAs (Chen et al., ; Gibis & Weiss, , ; Jinap, Hasnol, Sanny, & Jahurul, ; Natale, Gibis, Rodriguez‐Estrada, & Weiss, ; Oz & Cakmak, ; Oz & Kaya, ; Rounds, Havens, Feinstein, Friedman, & Ravishankar, ; Tengilimoglu‐Metin, Hamzalioglu, Gokmen, & Kizil, ; Viegas, Amaro, Ferreira, & Pinho, ; Zeng et al., ) have been proven to be useful for minimizing the formation of HAAs in various foodstuffs. However, to the best of our knowledge, there is a lack of systematic and comprehensive overview about mitigation strategies on the formation of HAAs in various foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, scientists around the world have recently focused on the investigation about how to reduce HAAs in heat‐processed foods and attempted to find possible strategies to inhibit the formation of HAAs (Chen et al., ; Oz & Seyyar, ; Rahman, Sahar, Khan, & Nadeem, ; Tengilimoglu‐Metin & Kizil, ). To date, several inhibitory strategies such as adjusting cooking methods (Guo et al., ; Oz & Kotan, ; Oz & Zikirov, ; Oz, Kaban, & Kaya, ; Soladoye et al., ), changing thermal treatments (Raza, Shabbir, Khan, Suleria, & Sultan, ; Shabbir, Raza, Anjum, Khan, & Suleria, ), adding antioxidants or substances which have inhibiting effect on the formation of HAAs (Chen et al., ; Gibis & Weiss, , ; Jinap, Hasnol, Sanny, & Jahurul, ; Natale, Gibis, Rodriguez‐Estrada, & Weiss, ; Oz & Cakmak, ; Oz & Kaya, ; Rounds, Havens, Feinstein, Friedman, & Ravishankar, ; Tengilimoglu‐Metin, Hamzalioglu, Gokmen, & Kizil, ; Viegas, Amaro, Ferreira, & Pinho, ; Zeng et al., ) have been proven to be useful for minimizing the formation of HAAs in various foodstuffs. However, to the best of our knowledge, there is a lack of systematic and comprehensive overview about mitigation strategies on the formation of HAAs in various foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Meat is usually marinated by soaking in an acidic solution to improve tenderness, taste, and smell [6], or to extend the shelf life of the product by limiting the growth of bacteria, especially pathogenic ones [8]. Many researchers attempt to use natural marinades such as lemon juice, lemon, pineapple marinades, potato tuber juice, soya sauce, wine sugar, organic acids, tamarind, lime, calamansi, and red wine [5,7,[9][10][11]. However, in the available literature, there are no reports on the use of fermented dairy products (FDP) for meat marinating.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al () reported that PhIP content decreased with ascending concentrations of Sichuan pepper and sanshoamide extracts in grilled ground beef patties. Additionally, Jinap, Hasnol, Sanny, and Jahurul, () stated that PhIP concentrations showed inverse correlation with the amount of added organic acid in marinades containing different types of sugar in grilled chicken. The other reports also stated the same results (Lu et al, ; Tengilimoglu‐Metin & Kizil, ).…”
Section: Resultsmentioning
confidence: 99%
“…Johansson and Jagerstad () showed that MeIQ was detected up to 1.3 ng/g in salmon deep‐fried (150°C) and Nd in smoked salmon. In addition, some authors described different contents of MeIQ in various processed meat (Jinap et al, ; Lu et al, ; Tengilimoglu‐Metin & Kizil, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation